2022
DOI: 10.3390/ijerph19159329
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Doping Prevalence and Socioeconomic Parameters: An Analysis by Sport Categories and World Areas

Abstract: Socioeconomic differences between countries, including corruption and doping scandals, have increased in the last few decades. The aims of the current investigation were to examine doping prevalence according to world areas and sport groups and its association with socioeconomic factors worldwide. The Anti-Doping Rule Violations (ADRVs) of 160 countries competing at 2016 Olympics were analyzed between 2013 and 2018. In addition, the relationship between doping prevalence and socioeconomic characteristics, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our research shows that global indexes significantly associate the number of transgression cases and their disclosure as a corporate scandal. Our findings are consistent with the work of Dorfleitner et al (2022) and Terreros et al (2022), who found a positive correlation between HDI and transgressions, as well as Terreros et al (2022) study, which saw a negative correlation between CPI and transgressions. Additionally, Aguiar et al (2019) and Gerged and Elheddad (2020) research suggests a positive association between HDI and governance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our research shows that global indexes significantly associate the number of transgression cases and their disclosure as a corporate scandal. Our findings are consistent with the work of Dorfleitner et al (2022) and Terreros et al (2022), who found a positive correlation between HDI and transgressions, as well as Terreros et al (2022) study, which saw a negative correlation between CPI and transgressions. Additionally, Aguiar et al (2019) and Gerged and Elheddad (2020) research suggests a positive association between HDI and governance.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of these studies are generally complex and inconclusive. However, some studies have found a negative correlation between low CPI values and higher reported transgressions (Terreros et al, 2022).…”
Section: Relationship Between Corporate Scandals and Country-level In...mentioning
confidence: 95%
See 2 more Smart Citations